RARE EARTH ELEMENT GEOCHEMISTRY OF LATE CENOZOIC VOLCANIC SERIES IN THE LESSER CAUCASUS - Imamverdiev N.A. (My University, 2003)
The rare earth element (REE) distribution in the Late Cenozoic volcanic series of the Lesser Caucasus is discussed. The origin of the Upper Miocene-Lower Pliocene andesite-dacite-rhyolite, Upper Pliocene-Lower Quaternary trahyrhyolite, and Upper Pliocene-Quaternary trachybasalt-trachyandesite rock associations was deduced from the REE patterns. It is assumed that the elevated REE, Sr, Ba, U, Th, and Rb contents in these rocks are caused by relatively low degrees of partial melting in the metasomatically altered mantle at a great depth. Rhyolite and trachyrhyolite from the trachyrhyolite association are characterized by a deep Eu minimum, indicating a relatively low degree of partial melting when considerable quantities of plagioclase and accessory minerals are left as restite. The mantle component of the Upper Pliocene-Quaternary subalkaline and alkaline basaltoids in the Lesser Caucasus is composed of metasomatized garnet Iherzolite; the degree of partial melting of the slightly metasomatized source is estimated to be 2.5-10%.
Keywords: Cenozoic; Cenozoic::Quaternary; Кайнозой::Четвертичная